A Novel Methodology for Calculating Crack Opening Stress under Tension-Compression Cyclic Load - Lin Zhang; Xiaohui Wei (Advances in Materials Science and Engineering)
Crack closure model has been used in several applications on the prediction of fatigue crack growth life, with expression of crack opening stress often serving as milestones. A typical difficulty in calculating the crack opening stress is the phenomenon of crack closure caused by the compressive load effect. Compressive load effect, resulting in the change of residual stress status at the unloading stage and the decrease of crack opening stress, is a long-term challenge for predicting fatigue crack growth life. We propose the expression of crack opening stress to predict fatigue crack growth life based on the analysis of compact tensile specimen with elastoplastic element method. It combines the characteristics of material and load to deal with the phenomenon of crack closure and uses stress ratio and normalized maximum applied load variable to construct the expression of crack opening stress. In the study of tensile-compression fatigue crack growth experiments, the proposed expression is proved to improve, by comparative analysis, the predictive ability on the whole range of experiment data. The novel expression is accurate and simple. Consequently, it is conducive to calculate the crack opening stress under tension-compression load.